The present adenomyosis treatment status in Luzhou, China: a small scope observational cross-sectional survey - Lingling Xie; Mengsi Yang; Xinyu Chen; Luxia Yao; Wei Xu; Qiuling Shi; Yuan Yuan (BMC Women's Health)
Abstract Objective To evaluate the current treatment status and management deficiencies of adenomyosis in Luzhou, China. Materials and methods A small-scale observational cross-sectional study of patients whose imaging suggests adenomyosis from July 2018 to February 2022 at a teaching hospital in Luzhou, China. All participants (1542 patients) completed a questionnaire of 14 items, including basic information, symptoms, treatment options, outcomes, and costs. The patients’ treatment options and the hysterectomy rate were evaluated. Results The treatment options of hormone agents included combined oral contraceptive pills (COCs), gonadotropin-releasing hormone analogues (GnRH-a), levonorgestrel-releasing intrauterine system (LNG-IUS), and dienogest for 2.07, 46.04, 63.49, and 4.67% of patients, respectively. The treatment options under uterus-sparing surgery included adenomyectomy and high-intensity focused ultrasound (HIFU) treatment, presenting in 3.76 and 33.27% of patients, respectively. Finally, 458 (29.70%) patients chose a hysterectomy. The hysterectomy rate between the hormone and uterus-sparing surgery sequential hormone groups (surgery group) was not significantly different (14.8 vs. 12.7%, χ2 = 0.344, P > 0.05). However, for the focal type and patients with > 24 months delayed treatment interval, the hysterectomy rate of the hormone group was significantly higher than that of the surgery group (8.5% vs. 1.3%, χ2 = 11.722, P < 0.01 and 26.7% vs. 18.5%, χ2 = 4.906, P < 0.05, respectively). Conclusions There were treatment delays and treatment selection bias in managing adenomyosis in Luzhou, China. Popular science education and early individualized hormone therapy are needed. Uterine-sparing surgery should be carefully selected.